Rules for engaging the earl - MacGregor, Janna (MacGregor, Janna. Widow rules., 2022)
In desperate need of a husband, young widow Constance Lysander, about to give birth to her late husband's child, offers the Earl of Sykeston, a war hero--and her childhood best friend--a marriage of convenience that becomes so much more.